PENGARUH PENAMBAHAN LIMBAH ABU CANGKANG KEMIRI DAN ABU BONGGOL JAGUNG TERHADAP UJI KUAT TEKAN PADA PAVING BLOCK - Dwi Nata, Oktavian; Dharmawansyah, Dedy (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2024)
Paving Block is a mixed composition consisting of cement, sand and water as a binding agent. In this research, we carried out an innovation in making paving blocks by utilizing waste candlenut shell ash and corncob ash with a substitute mixture of 25%, 5% candlenut shell ash and 15%, 5% corncob ash at CV Maras Beton Sumbawa. The aim of this research is to determine the compressive strength of paving blocks, visual defects in paving blocks and to determine the water absorption capacity of paving blocks with a test age of 28 days. Based on research results, the highest compressive strength of paving blocks was a mixture of 15% candlenut shell ash, 5% corncob ash with a compressive strength value of 20.41MPa. Meanwhile, the lowest strength value was found in a mixture of 25% candlenut shell ash and 15% corncob ash with a compressive strength value of 12.88 Mpa. Meanwhile, the maximum water absorption value was in a mixture of 15% candlenut shell ash and 15% corncob ash with a water absorption value of 6.67%. Meanwhile, the lowest water absorption value was a mixture of 15% candlenut shell ash and 5% corncob ash with a water absorption value of 10%. Meanwhile, visually defects in paving blocks are found in a mixture of 25% candlenut shell ash and 15% corncob ash, there are porosity defects or cavities on the surface of the paving block, resulting in a decrease in the compressive strength value. All variations of mixed substitutes meet the compressive strength standards and water absorption standards for paving blocks in accordance with standards (SNI 0691 – 1996) but only vary in the values ??of water absorption capacity and compressive strength.